Wpływ elementu tnącego na drgania emitowane przez kosy spalinowe do zarośli i trawy - Wójcik, Krzysztof (Leśne Prace Badawcze, 2015)
Generally, the choice of cutting element used in brush cutters for brush-woods and grasses depends on the type of work on one hand and the size of the engine on the other. However, at the same time, the use of individually chosen cutting elements entails a certain risk of vibration resulting from their varying design and size, which has a big impact on comfort and working time, but most importantly on operator health. The aim of the study is a preliminary analysis of the dangers due to vibration of brush cutters and to determine how the choice of the cutting element affects the intensity of the vibrations emitted by the machine. Furthermore, one aim was to determine the daily vibration exposure, relative to an equivalent value of vibration, experienced by the device operator. This study involved four models of brush cutters with three machines of each model, differing in size (displacement and engine power) and equipped with six different cutting elements. A vibration acceleration test was carried out in accordance with the applicable PN-EN ISO 5349-1 and 2:2004 and Directive 2002/44/EC. An analysis of the obtained results leads to the conclusion that the examined professional brush cutters emit vibrations of such intensity that the daily exposure limit (5 m ∙ s -2 ) is exceeded more than twofold. One cannot directly determine the influence on vibration intensity by the type of cutting element or the exhaust, but it should be noted that use of a cutting unit as recommended by the manufacturer creates less harmful vibrations, especially when the engine runs at the nominal rotational speed. In order to minimize the risk due to vibrations from brush cutters, engines with a cylinder capacity below 45 cm 3 are recommended to be equipped with trimmer heads and disk knives, while engines with over 50 cm 3 should run with circular saws.